RELATIONSHIP BETWEEN FAMILY INCOME, HEALTH CHECK-UP AND NUTRITIONAL STATUS OF BADJAO PREGNANT MOTHERS IN SOUTHEAST SULAWESI, INDONESIA - Hariani, Hariani; Paukiran, Tress; Taskawati, Saktian (Public Health of Indonesia, 2017)
Background: The nutritional status of pregnant women is strongly influenced by food intake and the presence of infectious diseases. Other factors that also affect the nutritional status of pregnant women are family income and health services. Objective: This study aims to identify the relationships between family income, health check-up, and nutritional status of Badjao pregnant mothers in Southeast Sulawesi, Indonesia. Methods: This was a correlational cross-sectional study, which was conducted in October 2013 in Lagasa Village, Duruka district, Muna regency. The population in this study is all pregnant women in Badjao tribe staying in the village of Lagasa, Duruka district, Muna regency, Southeast Sulawesi Province. There were 35 samples in this study selected using total samplingResults: Findings showed that there was statistically no significant relationship between income and nutritional status in pregnant mothers with p-value 0.259 (>0.05); and there was statistically significant relationship between health check-up and nutritional status in pregnant mothers with p-value 0.009 (<0.05).Conclusion: There is significant relationship between maternal health check up and nutritional status of Badjao pregnant mothers. it is suggested that the Badjao pregnant mothers should have complete health check-up to ensure they are in good condition and early detection for disease.